2013
DOI: 10.1183/09031936.00209212
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid as a predictor of mortality and future exacerbations of COPD

Abstract: Serum uric acid is increased in respiratory disease, especially in the presence of hypoxia and systemic inflammation. We evaluated serum uric acid as a biomarker for prediction of mortality and future acute exacerbation of chronic obstructive pulmonary disease (AECOPD).Serum uric acid was measured in 314 eligible consecutive patients on admission for AECOPD. Patients were evaluated monthly for 1 year.Uric acid levels were higher in patients with more severe airflow limitation and in those experiencing frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
88
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 41 publications
6
88
0
Order By: Relevance
“…The levels of eATP were elevated in the BAL of patients with COPD (44). Furthermore, serum UA correlated with 30-day mortality in patients with COPD exacerbations (45).…”
Section: Inflammasomes In Airways Diseasesmentioning
confidence: 99%
“…The levels of eATP were elevated in the BAL of patients with COPD (44). Furthermore, serum UA correlated with 30-day mortality in patients with COPD exacerbations (45).…”
Section: Inflammasomes In Airways Diseasesmentioning
confidence: 99%
“…Additionally, PaO 2 /FIO 2 was statistically significant lower in dead than in survived one, moreover, there was a statistically significant negative correlation between uric acid and PaO 2 /FIO 2 , meaning that ARDS patients with more hypoxemia had a higher serum uric acid level as well as both correlated inversely. These findings were explained by Bartziokas and his associates [7] who found that serum uric acid which is the final product of purine degradation, increases significantly during hypoxia which is a hall mark feature in ARDS patients. Also, Fabbri and Rabe [9] reported that impaired pulmonary function reduces oxygen intake resulting in tissue hypoxia which was more prominent during acute exacerbation in COPD and this may lead to increased circulating uric acid levels originating from both lung and peripheral tissue damage.…”
Section: Discussionmentioning
confidence: 84%
“…ARDS is a life threatening respiratory condition characterized by hypoxemia [4]. Serum uric acid levels increases significantly during hypoxia [7][8][9]. Elevated uric acid levels have been associated with the presence of systemic inflammation [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 There is data regarding the significance of serum uric acid level among patients with COPD. [8][9][10][11][12] Serum uric acid has been proposed as a marker of impaired oxidative metabolism and an independent prognostic marker in several cardio-vascular disorders such as congestive heart failure [13][14] pulmonary hypertension 15 and myocardial infarction and its related complications. [16][17] There are other biomarkers also which helps in assessing severity of COPD [18][19] but they are not easily available and are costlier also.…”
Section: Introductionmentioning
confidence: 99%